Mechanical characteristics of distributed electric wheel loader in shoveling condition - Fei, Xiaotao; Shenrui, Han; Voon Wong, Shaw; Azman, Muhammad Amin; Yunwu, Han (Universitas Muhammadiyah Magelang, 2023)
Multi-bridge centralized drive wheel loaders can produce parasitic power to waste energy and aggravate tire wear. Distributed Electric Wheel Loader(DEWL) is a new structure with two drive motors that can be controlled independently or in concert. Hence, this study investigates the mechanical characteristics of DEWL in its shoveling condition. Firstly, for the DEWL, dynamic models are established including running and shoveling conditions, on the basis of automobile theory. Secondly, a simplified structural model of DEWL is used to construct the mechanical equations, and the theoretical derivation is utilized to analyze the forces on wheels during different driving modes of running and shoveling conditions. Finally, the free shoveling of dry sands and gravel materials is tested by a ZL50GV-EV DEWL, and the drive forces of three drive modes on horizontal concrete pavement are tested. The results show that the parasitic power is generated when the driving motor has a larger speed than that of the other motor, which is caused by the movement of the loader's center of gravity. The driving torques generated by the motors are basically the same when the DEWL is in front-drive mode and rear-drive mode at the setting speed of 600rpm, whether it is running forward or backward, with a torque fluctuation of 0.16%-1.28% and a power fluctuation of 0.02%-1.29%. The DEWL consumes more power in dual-drive mode than in single drive if it is controlled in speed-target mode.